Multivariate Analysis and Warning of a Tornado Embedded in Tropical Cyclone in Southern China - Zhaoming Li (IEEE, 2021)
An EF1 tornado associated with tropical cyclone (TC) Ewiniar hit Dali Town, Foshan, Guangdong Province at 06:03 UTC on June 8, 2018, and the first special tornado warning was issued to five towns at 05:05 UTC. This article utilizes minute-scale observations from an X-band dual-polarization radar and measurements from an S-band Doppler radar to resolve the polarization characteristics associated with this tornado. In addition, second-scale atmospheric pressure data obtained from micropressure gauge and NCEP FNL (Final) Operational Global Analysis data are used to investigate the synoptic conditions and features of gravity waves (GWs). The conspicuous features of the descending reflectivity core, Doppler velocity couplet, Z $_{\text{DR}}$ arc, K $_{\text{DP}}$ foot, and the separation of the Z $_{\text{DR}}$ arc and K $_{\text{DP}}$ foot are detailed to quantify the tornadic evolution. The amplitude fluctuation of the GWs suddenly increased to 77.3 Pa, 2 h before the tornado occurred. Two focus regions with K $_{\text{DP}}$ values greater than 6 $^°$ /km are discussed by combining the Doppler velocity couplet and Z $_{\text{DR}}$ arc. The separation distance of the Z $_{\text{DR}}$ arc and K $_{\text{DP}}$ foot was approximately 2.1 km. The appearance of these features may be indicative of fundamental processes intrinsic to tornado storms.